LAJU PELEPASAN DIAZINON DARI MIKROKAPSUL BERBASIS MELAMIN FORMALDEHID - , NOVIANA UTAMI CIPTANINGTYAS SUHARTAYA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Microencapsulation of diazinon based on melamine formaldehyde could produce a product with controlled release properties, which gives the advantages namely efficient in the usage of diazinon and to reduce environment pollution. This research aims to study the effect of pH and temperature on the release rate of diazinon in aqueous medium. The release rate of diazinon profiles are represented by a rate of diffusion (N A ). In this research the microcapsule membrane was modified in two types, the first, melamine formaldehyde (MF) and the second types, melamine formaldehyde added with sodium dodecyl sulphate and polyvinyl alcohol (MF-SDSPVA). A number of microcapsules were immersed in distilled water to study the release rate of diazinon. During the immersion process, variables studied were implemented, which is pH (4, 5, 6, 7, and 8) and temperature (26, 35, 40, 45, and 50Â°C). Within a certain time interval water, samples were taken and analyzed to determine the concentration of diazinon until it reached equilibrium concentration. The results showed that the pH and temperature has little effect on the release rate of diazinon from microcapsule based on melamine formaldehyde. This is due to the diffusion through the microcapsule membrane is not influenced by the pH and temperature of the solution outside of microcapsule.